The Phenomenon of Code Mixing in Arabic Conversation at Pondok Pesantren Muthmainnatul Qulub al-Islami Cibinong Bogor - Ii Rahmanudin Rahmanudin (Nady Al-Adab : Jurnal Bahasa Arab, 2022)
Abstract This study aims to describe the phenomenon of code mixing between Sundanese code and Arabic code in Arabic conversation at Pondok Pesantren Muthmainnatul Qulub Al Islami Cibinong, Bogor, West Java. This study used descriptive qualitative method with a sociolinguistic approach. The data collection techniques are listening and interviewing. The results of this study are that the majority of female students mix or use local languages or Sundanese and even Indonesian into Arabic speech, both in sentence structure and language. With this research, educational institutions, especially Islamic boarding schools, can tighten regulations for female students to always use Arabic in accordance with good and correct structure, rules and language. Keywords: Bilingualism, Code Mixing, Arabic Language